Location of the complement factor H binding site on streptococcal M6 protein. - Fischetti, V A (1995)
The surface M protein of group A streptococci binds factor H, a regulatory protein of the alternative complement pathway, which may contribute to the antiphagocytic activity of the M molecules. To locate the factor H binding domain in the alpha-helical coiled-coil structure of the M molecule, the M protein was cleaved with pepsin at pH 5.8, which separates the molecule approximately in half. Western blot (immunoblot), amino acid sequence, and mass spectrometric analyses revealed that factor H bound to a 14.6-kDa C-terminal fragment of the M molecule. Competitive inhibition of factor H binding to the 14.6-kDa fragment with M protein peptides localized the binding site to amino acids 256 to 292. This segment is located within the surface-exposed region of the M6 protein, identified as the C-repeat region, whose sequence is conserved among heterologous M and M-like molecules. These studies also identified a second pepsin-susceptible site with the sequence ELAK located within the cell wall-associated region of the M molecule.